Photogrammetric approach to detect road pavement friction - Zdeneˇk Svatý; Pavel Vrtal; Roman Shults; Tomáš Kohout; Luboš Nouzovský; Tomáš Blodek; Karel Kocián (PLoS ONE, 2025)
This paper deals with evaluation of photogrammetric measurements of pavement macrotexture for the purposes of new non-contact method for determination of pavement skid resistance. The aim was to create a method that yields results comparable to existing pavement friction measurement techniques, particularly the sand method, and to assess whether the measurements obtained using the non-contact approach are equally effective. Additionally, the goal was to introduce and define limits for camera calibration applicable to similar cases of object measurements at close distances. Based on existing standards, specific pavement samples exhibiting various macrotexture qualities were selected. The authors conducted 23 different combinations of photogrammetric measurements based on their findings during the evaluations. A comparison of the applied procedures with a reference measurement using the sand method was made, and the measurement error rate was calculated. By evaluating the different variations of the road surface models created, it was concluded that the most reliable results for defining friction are obtained by interleaving the test specimen through a plane based on the principle of best fit using the four highest points of the macrotexture. The ideal size of the sub-areas for applying the mask is 7.5–10 mm. Photogrammetry has proven to be a suitable and accurate tool for assessing pavement surface texture and can be considered as a suitable alternative to other skid resistance measurement approaches.